An incompletely reacted bismuth calcium niobate material, a preparation method and application thereof

CN122877804APending Publication Date: 2026-10-09CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611011558.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]本发明旨在克服现有完全反应铌酸铋钙(CBN)催化活性低的缺陷,本发明的第一个目的在于提供一种不完全反应的铌酸铋钙材料的制备方法,本发明的制备方法,通过精准控制熔盐反应的烧结温度,使反应停留在特定的中间阶段,得到不完全反应中间态产物(命名为u-CBN),意外的发现,其催化性能远高于完全反应的纯相CBN

Benefits of technology

[0027]本发明颠覆了传统追求材料高纯、完全反应的思路,首次提出通过控制熔盐烧结温度进行不完全反应来制备铌酸铋钙中间态产物(u-CBN)。该方法操作简单,无需特殊设备,易于放大生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122877804A_ABST
    Figure CN122877804A_ABST
Patent Text Reader

Abstract

The application discloses an incompletely reacted bismuth calcium niobate material and a preparation method and application thereof. Raw material powder is mixed with molten salt powder to obtain mixed powder, the mixed powder is sintered at 750-800 DEG C for 0.5-1h to obtain a reaction product, and the reaction product is washed with water to obtain the bismuth calcium niobate material. The raw material powder is composed of calcium carbonate, bismuth trioxide and niobium pentoxide. According to the preparation method, the sintering temperature of the molten salt reaction is accurately controlled, the reaction is stopped at a specific intermediate stage, and an incompletely reacted intermediate product is obtained. It is unexpectedly found that the catalytic performance of the intermediate product is much higher than that of a completely reacted pure phase CBN.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of inorganic functional material preparation and environmental catalysis technology, specifically relating to an incompletely reacted bismuth calcium niobate material, its preparation method, and its application. Background Technology

[0002] Rapid industrialization has led to the overconsumption of traditional fossil fuels such as coal, oil, and natural gas, accompanied by the emission of harmful chemicals such as organic dyes, heavy metal ions, and pesticides, resulting in increasingly severe energy crises and environmental problems. Therefore, the capture, storage, and conversion of clean energy is urgently needed. In recent years, emerging catalytic technologies have emerged that utilize the photoelectric effect, piezoelectric effect, and pyroelectric effect to capture solar, mechanical, and thermal energy respectively, and apply them to the preparation and conversion of clean energy. Among these, photocatalysis technology has attracted much attention due to its use of clean, abundant, and renewable solar energy resources, and has been initially applied in multiple fields such as pollution control and energy conversion.

[0003] Photocatalysis refers to the process by which semiconductor materials generate electron-hole pairs under light excitation, and these pairs participate in redox reactions. The band gap structure of the photocatalyst, the separation efficiency of photogenerated carriers, and the surface reaction kinetics are crucial. To enhance the separation and migration efficiency of carriers during photocatalysis, photocatalysis is combined with the piezoelectric effect. The built-in electric field generated under external force suppresses the carrier shielding effect of photogenerated carriers, achieving a long-term enhanced photocatalytic effect. This method is called piezoelectric-photocatalytic synergistic catalysis. If a material possesses both piezoelectric response and photoelectric effect, such as BaTiO3 or ZnO, the piezoelectric potential generated under external force is sufficient to regulate the separation, migration, and redox reactions of its own photogenerated charges. This eliminates the need to construct a heterojunction by combining ferroelectric / piezoelectric materials with the photocatalyst to achieve piezoelectric-photocatalytic synergistic catalysis, greatly simplifying the synthesis process.

[0004] Calcium bismuth niobate (CaBi₂Nb₂O₉, CBN) is a typical bismuth-layered perovskite ferroelectric material, widely used in electronic ceramics, sensors, and memory due to its excellent ferroelectricity, piezoelectricity, and high-temperature stability. In recent years, researchers have discovered that CBN materials also show potential applications in the photocatalytic degradation of organic pollutants.

[0005] Traditional CBN materials are typically synthesized using solid-state reaction or molten salt methods, involving prolonged exposure to high temperatures (usually ≥1100℃) to obtain highly crystalline, pure-phase CBN powder. However, fully reacted CBN materials often suffer from limited surface active sites and high photogenerated electron-hole recombination rates, resulting in less than ideal photocatalytic degradation efficiency. Therefore, developing a CBN-based material with higher catalytic activity is of significant research value and practical importance. Summary of the Invention

[0006] This invention aims to overcome the low catalytic activity of existing fully reacted bismuth calcium niobate (CBN). The first objective of this invention is to provide a method for preparing an incompletely reacted bismuth calcium niobate material. The preparation method of this invention, by precisely controlling the sintering temperature of the molten salt reaction, keeps the reaction at a specific intermediate stage, obtaining an incompletely reacted intermediate product (named u-CBN). Unexpectedly, it was found that its catalytic performance is much higher than that of the fully reacted pure phase CBN.

[0007] The second objective of this invention is to provide an incompletely reacted bismuth calcium niobate material prepared by the above-described preparation method.

[0008] A third objective of this invention is to provide an application of an incompletely reacted bismuth calcium niobate material prepared by the above-described preparation method.

[0009] To achieve the above objectives, the present invention adopts the following technical solution:

[0010] This invention discloses a method for preparing an incompletely reacted bismuth calcium niobate material, wherein the raw material powder is mixed with molten salt powder to obtain a mixed powder, the mixed powder is sintered at 750-800 ℃ for 0.5-1 h to obtain a reaction product, and then washed with water to obtain the final product.

[0011] The raw material powder is composed of calcium carbonate (CaCO3), bismuth trioxide (Bi2O3), and niobium pentoxide (Nb2O5).

[0012] The method for preparing incompletely reacted bismuth calcium niobate material provided by this invention precisely controls the sintering temperature within the sintering range of this invention to obtain incompletely reacted, impure phase CBN. Experiments have shown that its catalytic performance is much higher than that of completely reacted pure phase CBN. However, experiments have also shown that the temperature of this invention needs to be strictly controlled within the range of this invention to obtain incompletely reacted, impure phase CBN with excellent catalytic performance. Experiments have also shown that if the temperature is below 750℃, the impurity phase content is too high, the crystallinity of the product is poor, the grains are difficult to form, and the catalytic performance is insufficient. If the temperature is too high, the impurity phase content is too low, and the catalytic performance is also reduced.

[0013] The preferred method involves accurately weighing calcium carbonate (CaCO3), bismuth trioxide (Bi2O3), and niobium pentoxide (Nb2O5) according to the theoretical molar ratio of calcium bismuth niobate (CaBi2Nb2O9) based on the chemical formula CaBi2Nb2O9. Specifically, the molar ratio of Ca:Bi:Nb is 1:2:2.

[0014] In a preferred embodiment, the molten salt powder is obtained by mixing sodium chloride (NaCl) and potassium chloride (KCl) in a molar ratio of 1-11:1, preferably 1-2:1.

[0015] In a preferred embodiment, the mass ratio of raw material powder to molten salt powder in the mixed powder is 0.3-4:1, preferably 0.8-1.2:1.

[0016] In a preferred embodiment, the mixing method is wet ball milling, wherein anhydrous ethanol is used as the dispersion medium and the wet ball milling time is 12-24 hours.

[0017] A uniformly mixed slurry was obtained by wet ball milling, and then dried at 70 °C to obtain a dry mixed powder.

[0018] In a preferred embodiment, the heating rate is controlled to be 2-5 °C / min during sintering.

[0019] In actual operation, the mixed powder is placed in an alumina crucible and then placed in a muffle furnace. The temperature is raised to the target sintering temperature of 750-800 ℃, which is lower than the temperature at which CBN reacts completely. This causes the reactants to undergo an incomplete reaction, resulting in an incompletely reacted bismuth calcium niobate intermediate. After the holding time is completed, the furnace is cooled to room temperature.

[0020] The reaction product was then removed and repeatedly washed and filtered with deionized water to remove water-soluble molten salts (NaCl / KCl). The product was then dried at 70 °C to obtain incompletely reacted bismuth calcium niobate material (u-CBN).

[0021] Experiments have shown that if the obtained reaction product is added to a dilute nitric acid solution (1 mol / L) and soaked at room temperature for 12 hours to dissolve unreacted impurities such as Bi2O3 and CaO, and then washed with deionized water until neutral, and then filtered and dried to obtain pure phase bismuth calcium niobate (CBN), its catalytic activity is much lower than that of the incompletely reacted bismuth calcium niobate material obtained by simply washing with water.

[0022] The present invention also provides an incompletely reacted bismuth calcium niobate material prepared by the above preparation method.

[0023] The present invention also provides the application of the incompletely reacted bismuth calcium niobate material prepared by the above preparation method, wherein the bismuth calcium niobate material is used for the catalytic degradation of organic dye wastewater.

[0024] Especially its application in simulating the decreasing solution of Rhodamine B (RhB) under alternating sunlight and stress.

[0025] The specific application method is as follows: u-CBN is dispersed as a photocatalyst in an aqueous solution containing RhB at a catalyst concentration of 0.5 g / L. After stirring in the dark for 30 minutes to reach adsorption-desorption equilibrium, the light source is turned on for irradiation and ultrasonic vibration. Samples are taken at regular intervals to measure the change in RhB concentration. The degradation rate constant of u-CBN for RhB is significantly higher than that of pure phase CBN after complete reaction.

[0026] Beneficial results

[0027] This invention overturns the traditional approach of pursuing high-purity materials and complete reactions, proposing for the first time to prepare bismuth calcium niobate intermediates (u-CBN) through incomplete reactions by controlling the molten salt sintering temperature. This method is simple to operate, requires no special equipment, and is easy to scale up for production.

[0028] Significantly enhanced catalytic activity: Experiments confirmed that the catalytic degradation rate of Rhodamine B (RhB) by incompletely reacted u-CBN was much higher than that of pure-phase CBN obtained by acid washing after complete reaction. The hypothesized mechanism is that unreacted Bi₂O₃, Nb₂O₅, or intermediate amorphous interfaces exist on the u-CBN surface. These components may promote the separation of photogenerated carriers or provide additional surface active sites, thereby greatly improving the degradation efficiency.

[0029] Due to the lower sintering temperature and shorter holding time, the method of this invention significantly reduces energy consumption, shortens the production cycle, and lowers costs compared to the traditional complete reaction synthesis of CBN.

[0030] Bismuth calcium niobate exhibits both piezoelectric response and photoelectric effect. The piezoelectric potential generated under external force is sufficient to regulate the separation, migration, and redox reactions of its own photogenerated charges. Piezoelectric-photocatalytic synergistic catalysis can be achieved without constructing a heterojunction by combining ferroelectric / piezoelectric materials with photocatalysts, greatly simplifying the synthesis process.

[0031] This invention directly addresses the problem of dye degradation in the field of water treatment, providing a low-cost and efficient candidate photocatalyst with clear prospects for industrial application. Attached Figure Description

[0032] Figure 1 The X-ray diffraction (XRD) comparison patterns of u-CBN-800℃ (incomplete reaction, unwashed) prepared in Example 1 of the present invention and pure phase CBN-800℃ (incomplete reaction, washed) prepared in Comparative Example 1 are shown.

[0033] Figure 2 The X-ray diffraction (XRD) comparison patterns of u-CBN-750℃ (incomplete reaction, unwashed) prepared in Example 2 of the present invention and pure phase CBN-750℃ (incomplete reaction, washed) prepared in Comparative Example 1 are shown.

[0034] Figure 3 X-ray diffraction (XRD) comparison patterns of u-CBN-800℃ prepared in Example 1, u-CBN-750℃ prepared in Example 2, and CBN-850℃ and CBN-900℃ prepared in Comparative Example 1.

[0035] Figure 4The graph shows a comparison of the degradation curves of rhodamine B (RhB) prepared by u-CBN-800℃ in Example 1 and pure phase CBN-800℃ in Comparative Example 1 under simulated sunlight (the horizontal axis represents the illumination time, and the vertical axis represents the residual dye concentration ratio C / C0).

[0036] Figure 5 The pseudo-first-order kinetic fitting curves and rate constants of the degradation of RhB by u-CBN-800℃ prepared in Example 1 of the present invention and the pure phase CBN-800℃ prepared in Comparative Example 1 are shown in the figure.

[0037] Figure 6 The graph shows a comparison of the degradation curves of rhodamine B (RhB) prepared by u-CBN-750℃ in Example 2 of the present invention and the pure phase CBN-750℃ prepared in Comparative Example 1 under simulated sunlight (the horizontal axis is the illumination time, and the vertical axis is the residual dye concentration ratio C / C0).

[0038] Figure 7 The pseudo-first-order kinetic fitting curves and rate constants of the degradation of RhB by u-CBN-750℃ prepared in Example 2 of the present invention and the pure phase CBN-750℃ prepared in Comparative Example 1 are shown in the figure. Detailed Implementation

[0039] Example 1: Preparation of u-CBN

[0040] Weigh out CaCO3 (2.00 g, 0.02 mol), Bi2O3 (9.32 g, 0.02 mol), and Nb2O5 (5.32 g, 0.02 mol) according to the stoichiometric ratio of CaBi2Nb2O9. Separately weigh out NaCl (7.31 g) and KCl (9.32 g) as molten salt, with the total mass ratio of molten salt to total raw materials approximately 1:1.

[0041] The weighed raw materials and molten salt were placed together in a ball mill jar, and anhydrous ethanol was added as a dispersion medium. The mixture was ground and mixed thoroughly for 24 hours until the slurry was homogeneous. Then, it was dried at 70 °C to obtain a mixed dry powder.

[0042] The mixed dry powder was placed in an alumina crucible and then placed in a muffle furnace. The furnace was heated to the target sintering temperature of 800 °C at a heating rate of 5 °C / min and held at this temperature for 1 hour to allow incomplete reaction of the reactants, yielding an incompletely reacted calcium bismuth niobate intermediate, named u-CBN-800℃. After the holding period, the furnace was cooled to room temperature.

[0043] The obtained u-CBN bulk material was removed, repeatedly washed with deionized water, and filtered to remove water-soluble molten salts (NaCl / KCl). The product was then dried at 70 °C.

[0044] Example 2: Comparison of different sintering temperatures

[0045] The other steps were the same as in Example 1, except that the sintering temperature in step 3 was changed to 750℃, resulting in u-CBN samples with different degrees of reaction at 750℃. Tests showed that the degradation rate of RhB was significantly higher than that of pure-phase CBN, but the sample prepared at 800℃ exhibited the highest activity.

[0046] Comparative Example 1: Preparation of pure phase CBN (acid washing, complete reaction)

[0047] Acid washing and purification: To further obtain pure-phase CBN for performance comparison, some dried u-CBN-800℃ and u-CBN-750℃ samples were taken and soaked in dilute nitric acid solution (1 mol / L) for 12 hours at room temperature to dissolve unreacted impurities such as Bi₂O₃ and CaO. Then, they were washed with deionized water until neutral, filtered, and dried to obtain pure-phase bismuth calcium niobate, named CBN-800℃ and CBN-750℃.

[0048] Complete reaction: In order to improve crystallinity and promote complete reaction, the sintering temperature was increased to 850°C and 900°C using the same raw material ratio as in Example 1, and held for 1 hour to obtain highly crystalline CBN-850°C and CBN-900°C.

[0049] Performance test example: Piezoelectric photocatalytic degradation of RhB

[0050] 50 mg each of u-CBN-800℃ prepared in Example 1, u-CBN-750℃ prepared in Example 2, and pure-phase CBN-800℃, CBN-750℃, CBN-850℃, and CBN-900℃ prepared in Comparative Example 1 were dispersed in 100 mL of a 10 mg / L Rhodamine B (RhB) aqueous solution. After stirring in the dark for 30 minutes to reach adsorption-desorption equilibrium, ultrasonic vibration at a frequency of 45 kHz and a power of 200 W was applied using an ultrasonic cleaner, and natural light irradiation (300 W) was simulated using a xenon lamp. The piezoelectric photocatalytic performance was tested under these conditions. During the catalytic process, 5 mL of the suspension at the same time interval was taken, centrifuged at 9000 r / min for 5 min, and the supernatant was extracted. The absorbance of the supernatant at 554 nm was measured using a UV-Vis spectrophotometer, and the remaining RhB concentration fraction C / C0 was calculated.

[0051] result:

[0052] After 60 seconds of light exposure, the RhB degradation rate of the u-CBN-800℃ group reached over 98%.

[0053] After 60 seconds of light exposure, the degradation rate of RhB in the pure phase CBN of Comparative Example 1 at 800℃ was only about 60%.

[0054] The pseudo-first-order kinetic fitting results show that the reaction rate constant of u-CBN at 800℃ is 0.0705 s⁻¹. -1 The rate constant of pure-phase CBN at 800℃ is only 0.0190 min s. -1 The former is about 3.7 times that of the latter.

[0055] After 60 seconds of light exposure, the RhB degradation rate of the u-CBN-750℃ group reached over 96%.

[0056] After 60 seconds of light exposure, the degradation rate of RhB in the pure phase CBN of Comparative Example 1 at 750℃ was only about 13%.

[0057] The pseudo-first-order kinetic fitting results show that the reaction rate constant of u-CBN at 750℃ is 0.0517 s⁻¹. -1 The rate constant of pure-phase CBN at 750℃ is only 0.0019 min s. -1 The former is approximately 27.2 times that of the latter.

[0058] After 60 seconds of light exposure, the RhB degradation rate in the CBN-850℃ group reached 35%, while the RhB degradation rate in the CBN-900℃ group reached 8%.

[0059] The pseudo-first-order kinetic fitting results show that the reaction rate constant of CBN at 850℃ is 0.0129 s⁻¹. -1 The rate constant of CBN-900℃ is 0.00144 s. -1 .

[0060] The results fully demonstrate that the u-CBN prepared by the incomplete reaction strategy described in this invention has outstanding advantages in catalytic degradation.

Claims

1. A method for preparing an incompletely reacted bismuth calcium niobate material, characterized in that: The raw material powder is mixed with molten salt powder to obtain a mixed powder. The mixed powder is sintered at 750-800 ℃ for 0.5-1 h to obtain the reaction product, which is then washed with water. The raw material powder is composed of calcium carbonate, bismuth trioxide and niobium pentoxide.

2. The method for preparing an incompletely reacted bismuth calcium niobate material according to claim 1, characterized in that: Based on the chemical formula of calcium bismuth niobate CaBi₂Nb₂O₉, calcium carbonate, bismuth trioxide, and niobium pentoxide were prepared according to the theoretical molar ratio.

3. The method for preparing an incompletely reacted bismuth calcium niobate material according to claim 1, characterized in that: The molten salt powder is obtained by mixing sodium chloride and potassium chloride in a molar ratio of 1-11:

1.

4. The method for preparing an incompletely reacted bismuth calcium niobate material according to claim 1, characterized in that: In the mixed powder, the mass ratio of raw material powder to molten salt powder is 0.3-4:

1.

5. The method for preparing an incompletely reacted bismuth calcium niobate material according to claim 1, characterized in that: The mixing method is wet ball milling, in which anhydrous ethanol is used as the dispersion medium and the wet ball milling time is 12-24 hours.

6. The method for preparing an incompletely reacted bismuth calcium niobate material according to claim 1, characterized in that: During the sintering process, the heating rate is controlled at 2-5 ℃ / min.

7. The incompletely reacted bismuth calcium niobate material prepared by the preparation method according to any one of claims 1-6.

8. The application of the incompletely reacted bismuth calcium niobate material prepared by the preparation method according to any one of claims 1-6, characterized in that: The bismuth calcium niobate material is used for the catalytic degradation of organic dye wastewater.